ASSESSMENT TINGKAT STRES KERJA DOSEN UNIVERSITAS DIPONEGORO SEMARANGTAHUN 2016 - Akrimna Fiddaraini; Hanifa Maher Denny; Ida Wahyuni; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
University is the main pillar that serves as a buffer of Human Resources (HR) quality where its success assessed by development and guidance to the lecturers. Based on the Strategic Plan Diponegoro University in year 2015-2019, the weaknesses of Diponegoro University as a Research University were the lecturers development. If the lecturer could not adjust itself with the demands, duty, responsibility, environmental conditions and other precipitating factors so it will be susceptible to get stress. Stress was defined as a condition that occured as a result of interaction between the individual work, where there was a mismatch characteristics and changes in the company. This research aimed to analyze the correlation between individual factors and work factors on the level of work stress toward Diponegoro University lecturers. The type of research was analytic with cross sectional approach. The sample in this study use Proportionate Stratified Random Sampling so that the respondents are 91 lectures. Based on the statistical test that using chi square test and Rank Spearman, variables that related to the level of work stress were role conflict (p value: 0.008), role ambiguity (p value: 0.002), and the work load (p value: 0.009). Meanwhile the variable that not related to the level of work stress were age (p value: 0.105), gender (p value: 0.355), work time (p value: 0.120) and responsibility (p value: 0.237). The researcher suggests to the lecturers to improve effective communication, work motivation and to the Diponegoro University to mapping the work load.